Dominance of Scorpaena maderensis among scorpaenids of littoral rocky reefs in Corsica (NW Mediterranean): Further evidence of Mediterranean Sea warming. Issue 2 (20th December 2021) - Astruch, Patrick; Belloni, Bruno; Rouanet, Elodie; Schohn, Thomas; Harmelin‐Vivien, Mireille; Harmelin, Jean‐Georges; Boudouresque, Charles‐François
Abstract: The population of Scorpaenidae was investigated in the Nature Reserve of Scàndula (Corsica, France, NW Mediterranean). While absent from Corsica a few decades ago, the Madeira rockfish Scorpaena maderensis is now the most abundant scorpaenid species in shallow rocky reef areas, far outnumbering Scorpaena notata and Scorpaena porcus . Considered as a subtropical species of Atlantic origin, the northward progression of the thermophilic S. maderensis and its dominance in Corsican waters is further evidence of the ongoing warming of the Mediterranean Sea.